Analisis Forensik Rekayasa Dokumen Digital dengan Metode NIST - Arizona Firdonsyah; Danur Wijayanto (INFORMAL: Informatics Journal, 2022)
Digital Forensics is one of the technological fields contained many sub-fields that can assist technically in collecting digital evidence to be presented in a trial in accordance with applicable law. The example of digital forensics sub-field is Image Forensics, which aims to digitally collect and look for evidentiary facts in determining the authenticity of an image or document that contained images. Various criminal and pornographic cases involving image files are still happening nowadays, therefore forensics on images as evidence is an important key to assist the court in making decisions. This research examines the authenticity of documents in the form of digital letters using National Institute of Standard and Technology (NIST) method by applying the forensic ELA (Error Level Analysis). Several previous researches have proven that the forensic ELA is able to detect modifications that have been made to images. Differences with previous researches and this research are the authors also checked the metadata of the images before performing the ELA examination using Fotoforensics. The results of the analysis shows a high level of consistency in the images and writings due to the accumulation of white dots in several places such as in headers, logos, header’s writings, text contents, footnotes, and signatures.